Statinotherapy – the paradigm of prevention and treatment of atherosclerotic pathology (focus on atorvastatin) - R. G. Oganov; D. M. Aronov; M. G. Bubnova (Кардиоваскулярная терапия и профилактика, 2006)
The authors discuss statinotherapy perspectives for secondary prevention, emphasizing statins’ effectiveness due to their high hypolipidemic activity and multiple pleiotropic effects. Aim. To study hypolipidemic activity and safety of generic atorvastatin (Liptonorm®), in comparison to original atorvastatin, Liprimar®. Material and methods. Thirty patients with coronary heart disease (CHD) and hypercholesterolemia (HCH) were randomized to 12-week original or generic atorvastatin treatment. Blood lipids, hepatic enzymes, and kreatine phosphokinase levels were measured. Results. Total cholesterol (TCH) levels in Liptonorm® and Liprimar® groups reduced from 7,7±1,25 to 4,4±0,8 mmol/l and from 6,9±1,3 to 4,6±0,7 mmol/l, respectively; low-density lipoprotein CH levels reduced from 5,4±1,4 to 2,7±0,7 mmol/l and from 4,7±1,3 to 2,7±0,7 mmol/l, respectively; triglycerides’ levels reduced from 1,7±0,7 to 1,2±0,3 mmol/l and from 1,9±1,0 to 1,2±0,4 mmol/l, respectively. High-density lipoprotein CH levels increased from 1,03±0,25 to 1,13±0,21 mmol/l and from 1,32±0,31 to 1,37±0,28 mmol/l, respectively. Lipid profile dynamics throughout the study was significant and similar in both groups; enzyme levels remained virtually Conclusion. Atorvastatin generic Liptonorm® demonstrated blood lipid effects similar to those for original atorvastatin.